Reserved Character: Shorthand and the Immortality Topos in Shakespeare's Sonnets. - Wilder, Lina Perkins (Studies in Philology)
Shakespeare's sonnets lay claim to a quality of liveliness as both an effect of reading and an intrinsic feature of the verse that parallels the physical life of the human body. In this essay, I will argue that the term character provides one way to conceptualize both the sonnets' internal aspirations to immortality and the ways in which successive generations of readers participate in perpetuating their and their addressee's life, allowing the poems to create a temporal and physical present for themselves. The sonnets' treatment of the term character —and particularly their implicit allusions to the fashionable new skill of shorthand transcription of "taking by charactery"—highlights the practical and ethical challenges of locating poetic immortality between the engagement of readers and the liveness, and liveliness, of verse. As recording technology and as a method of writing that combines idiosyncrasy and, paradoxically, both secrecy and openness, shorthand provides a theoretical model for reading Shakespeare's sonnets. Understanding Shakespeare's use of the term character has broad implications not only for our understanding of the immortality topos but also for theories of reading and writing.